Optimistic effects of dual nano-encapsulated probiotics on breeders laying performance, intestinal barrier functions, immunity and resistance against Salmonella Typhimurium challenge - Mohamed Tharwat Elabbasy; Asmaa T. Y. Kishawy; Walaa S. Abdelaziz; Ahmed Abdelfattah Hassan; Hend S. Nada; Reham A. Elbhnsawy; Amany M. Shosha; Dina Ibrahim; Fatma Eldemery; Shimaa A. E. Atwa; Wafaa R. I. A. Sherief; Eman S. El-Shetry; et al. (Scientific Reports)
Abstract Dual nano encapsulation of multi-strain probiotic bacteria can enhance their viability within the avian gastrointestinal tract and improve their effectiveness in disease prevention. So that this study spotted the light on the effect of dual nano encapsulated multi strain of probiotics (LEBB-NPs) contained Enterococcus faecium NCTC 7171, Bacillus amyloliquefaciens probiotic CECT 5940, Lacticasei bacillus casei ATTC334 and Bifidobacterium breve JCM1192 on laying performance, egg quality, immune defence, and resistance against Salmonella Typhimurium challenge. A total of 250 Ross 308 laying breeder hens, 20 weeks of age, were randomly allocated into five experimental groups (five replicates per group; 10 hens per replicate). The control group received a basal diet only and was not challenged. Infected control: hens received basal diet only and challenged with S. Typhimurium (1 × 106 CFU/hen) at week 34 of age. Groups LEBB-NPsI, LEBB-NPsII and LEBB-NPsIII fed basal diet supplemented with dual nano encapsulated multi strain of probiotics at levels of 1 × 106 CFU/kg diet, 1 × 108 CFU/kg diet and 1 × 1010 CFU/kg diet respectively and challenged with Salmonella Typhimurium (1 × 106 CFU/hen) at weeks 34 of age. The results indicated that hens receiving LEBB-NPs showed improved egg production and net feed efficiency during the pre-challenge and early laying periods. Additionally, they restored normal egg production performance following the challenge during the mid-laying period. Challenge at 34 weeks with S. Typhimurium had prominently decreased fertility, hatchability and increased egg embryonic death while dietary fortification with LEBB-NPsIII restored these parameters to normal levels. Dietary supplementation with LEBB-NPs enhanced immune defense, as evidenced by increased phagocytic activity, higher levels of IgM, IgG, lysozymes, and complement C3, both before and after the challenge. Furthermore, upregulation of tight junction genes (JAM, MUC-2, ZO-1, ZO-2, OCLN, and cldn-4), anti-inflammatory mediators (IL-4 and IL-10), and avian β defensinins (AvBD6 and AvBD6) expression levels was noticed before and after challenge in all groups fed LEBB-NPs especially in LEBB-NPsIII fed group. Additionally, the expression of inflammatory mediators (IL-1β, IL-6, TNF-α, CCL4, CCL20 and iNos) had been down regulated in groups supplemented by LEBB-NPs compared to infected control group. A noticeable decrease in S. Typhimurium counts was observed at various intervals post-infection in the cecum, feces, liver, ovaries, and eggs in groups fed LEBB-NPs, particularly in the LEBB-NPsIII group. This reduction was accompanied by inhibition of virulence-related genes (HilA and SopD), compared to the infected control group. Overall, the encouraging results obtained from LEBB-NPs suggest their potential application in breeder feed, due to their positive effects on egg production, egg fertility, and hatchability, as well as their stimulatory role in immune defense and resistance to S. Typhimurium challenge.